Pemanfaatan Ekstrak Daun Lerek sebagai Antibakteri terhadap Bakteri Penyebab Jerawat Propionibacterium Acnes - Gita Susanti; Muhammad Asrul; Suci Tusnani (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2022)
Acne vulgaris (AV) is an inflammatory disease that caused by excessive activity in sebaceous glands and aggravated by Propionibacterium acnes infection. Synthetic antibiotics such as clindamycin are often used in the treatment of acne vulgaris, but its use can cause irritation, resistance, organ damage, and immunohipersensitivity. This study was performed to determine the antibacterial concentration of Lerek leaf ethanolic extract to P. acnes as involved in acne inflammation and pathogenesis. The phytochemical screening of the ethanolic extract of lerek leaf was performed using standard procedures. The extracts were tested for determining minimum inhibitory concentration value (MIC) using macrodilution method. Evaluation of its antibacterial effect to P. acnes growth inhibition was conducted using a plate count method with varying extract concentrations as follows: 4, 8, 16, and 32% w/v. The phytochemical analysis of the lerek leaf extract revealed the presence of flavonoids, tannin, alkaloid, terpenoid, saponin, and polyphenolic compounds. The MIC concentration of testing extracts against P. acnes ranged from 32% w/v to 16% w/v. The results showed that the extract at 32% w/v was obtained P. acnes survival of 1.71%. It can be concluded that the lerek leaf ethanolic extract is a potential antibacterial to P. acnes.